Сьӧлыктэм сьӧлык: кузьмадёсъёс, веросъёс / Анатолий Перевозчиков - Перевозчиков Анатолий Аркадьевич (Удмуртия, 2017)
Экземпляры: СБ (20190627) / Инвентарный номер: 58062 / Цена: 150.00 / Сис.шифр: С(удм) / Авт.знак: П 27 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Удм)